Histoires et mémoires de l’exil et du retour des réfugiés Chiliens, des enjeux pour la société chilienne à travers l’exemple de la diaspora en France - Nicolas Prognon (Amnis)
Chile has become a paradigm of the complexity of the relations between past and present, and between memories and history. After the September 11, 1973 coup, around one million people left Chile. The journeys of the exiles and the retornados intertwine in the twists and turns of this story. These weakened ties between past and present are a challenge for the Chilean society. This diaspora is an integral part of the national collective memory constructed by the dictatorship, and of the imaginary consubstantial with international solidarity. The recovery of their stories, the recognition of their memories and of their identities are topical issues for the victims of the dictatorship, and therfore of the transition.